2007
DOI: 10.1038/sj.ijo.0803721
|View full text |Cite
|
Sign up to set email alerts
|

Nine-year incidence of obesity and overweight in an African-origin population

Abstract: This study highlights the high incidence of obesity/overweight in this cohort and suggests that the future public health burden of excess weight and its associated comorbidities may be elevated in this population of African origin. The development of strategies and interventions for the prevention and treatment of obesity/overweight are therefore of primary and immediate importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…The gradual increase in the incidence of overweight and obesity over time indicates that the greater prevalence rates are not just a recent trend (Parikh et al, 2007). Similar results reporting a higher annual overweight incidence rate (2.6%) than obesity (1.1%) were found in an African population (Nemesure et al, 2008) rates among women almost twice that of men. Direct comparisons with other studies as regards annual incidences should be interpreted with caution and have been used here strictly for comparative purposes.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The gradual increase in the incidence of overweight and obesity over time indicates that the greater prevalence rates are not just a recent trend (Parikh et al, 2007). Similar results reporting a higher annual overweight incidence rate (2.6%) than obesity (1.1%) were found in an African population (Nemesure et al, 2008) rates among women almost twice that of men. Direct comparisons with other studies as regards annual incidences should be interpreted with caution and have been used here strictly for comparative purposes.…”
Section: Discussionsupporting
confidence: 76%
“…However, these data are of a cross-sectional nature or the result of trend studies which compare prevalence rates reported in surveys with independent samples over time. Prevalence data do not provide estimates on incidence nor on the causal relationship between obesity and its associated factors, thus making it difficult to target those at highest risk (Nemesure et al, 2008). More long-term follow-up is required to allow a rigorous evaluation of the temporal relations between exposure and disease risk (Mujahid et al, 2005;Williamson et al, 1991;Vasan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropometric measurements [including height, weight, body-mass index (BMI), waist circumference (WC), hip circumference (HC) and waist–hip ratio (WHR)] above the upper quintile were considered high, those below the lowest quintile were classified as low and all others were defined as intermediate. Although standard cutpoints for these variables have been defined, the distribution of body size in Barbados is somewhat different than in other populations 10,11. As such, quintiles were chosen to better quantify these measurements.…”
Section: Methodsmentioning
confidence: 99%
“…African-Barbadians have similar characteristic patterns of body size and fat distribution as African-Americans, with lower visceral and more subcutaneous fat than populations of European descent (3,4). While it has been postulated that obesity plays a role in the pathogenesis of prostate cancer, there is conflicting evidence on the relationship between prostate cancer and body size (5)(6)(7).…”
Section: Introductionmentioning
confidence: 94%